Experiência literária no ensino médico: estudo comparado Brasil - Uruguai - Basso, Elsa Mónica Bonito (My University, 2020)
This thesis proposes to analyse and compare the literary experience in formal education, of students of second and third year of High School, in Rio Grande do Sul (Brazil), and of the last year of Bachillerato diversificado in Uruguay. The piece of research, characterized as a comparative study, aims at 1) analysing the main characteristics of national and international public policies in Uruguay and Brazil, specifically in Rio Grande do Sul, 2) analysing curricula and schedules, specific literature syllabus, of High School in Rio Grande do Sul and Bachillerato diversificado in Uruguay, 3) analysing the voice of literature students and teachers of the above mentioned levels in both countries to, finally, 4) suggesting reflections and actions, with the aim of approximating cultures and experiences in the area of literature. Considering literature and literary experience as a text, interactions and possibilities emerging from this inter-relationship as a context, and the proposal of an effective interaction, aiming at literary experience as a paratext, this work presents a panorama of literature teaching in both countries. Approaching research in comparative education, based on authors as Shriewer (2018) and Landman (2008), founded on Dewey’s (1971, 2007) concept of education, it reflects on the formation of Latin-American pedagogic thinking. Considering these theoretical reflections, document analysis, quantitative and qualitative data, and students’ and teachers’ reports (obtained from the instruments used, based on discursive textual analysis), a significant socio-cultural approximation is noted among Brazilian and ruguayan participants; this is not what happens in terms of literary experience. The reasons for this are explained, and some examples of attempts of approximation already made and concrete proposals, such as international seminars and interaction between peers are presented. It appears that there is room for such interactions because they are provided, in one way or another, in the legislation itself, together with the interest shown by both students and teachers that they happen. The possibility of reflecting and working specificity of the area of comparative education, of teaching literature, and of high school students’ understanding of the world is evident.
Esta tese propõe analisar e comparar a experiência literária no ensino formal, de estudantes de segundo e terceiro ano de Ensino Médio, no Rio Grande do Sul (Brasil), e do último ano do Bachillerato diversificado, no Uruguai. A investigação, caracterizada como estudo comparado, busca 1) analisar as principais características de algumas políticas públicas internacionais e nacionais do Uruguai e do Brasil, especificamente, do Rio Grande do Sul, 2) analisar currículos e programas específicos de literatura, de Ensino Médio, no Rio Grande do Sul e no Uruguai, 3) analisar a voz de alunos de Ensino Médio e de professores de literatura de ambos países para, finalmente 4) propor reflexões e ações, visando à aproximação de culturas e experiências na área da literatura. Considerando a experiência literária e o mundo da literatura como um texto, as interações e possibilidades que surgem na inter-relação como contexto e a proposta de uma interação efetiva, com vistas à convivência literária, como paratexto, este trabalho apresenta um panorama do ensino de literatura em ambos países. Com abordagem de pesquisa em educação comparada, fundamentada em autores como Shriewer (2018) e Landman (2008), sustentada pela concepção de educação de Dewey (1971, 2007), reflete sobre a formação do pensamento pedagógico latino-americano. No que tange ao ensino e à aprendizagem de literatura, a partir dessas reflexões teóricas, análise dos documentos, dados quantitativos, qualitativos e relatos de alunos e de professores (levantados a partir dos instrumentos utilizados e tratados com base em análise textual discursiva), constata-se que existe uma aproximação sociocultural significativa entre os participantes uruguaios e brasileiros, que não abrange a experiência literária. São expostos os motivos pelos quais isso acontece e apresentam-se alguns exemplos de tentativas de aproximação já realizados e propostas concretas, como seminários internacionais e interação entre pares. Verifica-se que há espaço para tais interações por estarem previstas, de uma ou outra forma, na própria legislação e pelo interesse demonstrado tanto pela parte de alunos quanto de professores de que ela aconteça. A possibilidade de refletir e trabalhar especificidades da área de educação comparada, do ensino da literatura e da compreensão de mundo do aluno de ensino médio fica evidenciada.
Keywords: Literatura - Estudo e ensino (Ensino médio); Ensino médio - Estudos comparados; Estudo comparado - Brasil - Uruguai; Literature - Study and teaching (High school); High school - Comparative studies; Comparative Study - Brazil - Uruguay